1991
DOI: 10.2527/1991.6952050x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute thermal stress and amount of feed intake on concentrations of somatotropin, insulin-like growth factor (IGF)-I and IGF-II, and thyroid hormones in plasma of lactating Holstein cows2

Abstract: Our objective was to evaluate effects of acute thermal stress, independent of reduced feed intake caused by elevated temperatures, and of reduced feed intake in thermal comfort on plasma concentrations of somatotropin, insulin-like growth factors I and II, thyroxine, and triiodothyronine. Six Holstein cows (averaging 475 +/- 18 kg BW, 2.3 +/- .3 parities, and 96 +/- 12 d in lactation) surgically fitted with catheters in the hepatic portal vein, mesenteric vein, and intercostalis posterior artery were exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 0 publications
4
49
1
3
Order By: Relevance
“…Thyroid hormones tended to decrease during feed restriction [65]. From recent epidemiological studies, thyroid hormones are suggested to play a role in the onset of ovarian activity.…”
Section: A Role For Thyroid Hormonesmentioning
confidence: 97%
See 1 more Smart Citation
“…Thyroid hormones tended to decrease during feed restriction [65]. From recent epidemiological studies, thyroid hormones are suggested to play a role in the onset of ovarian activity.…”
Section: A Role For Thyroid Hormonesmentioning
confidence: 97%
“…Because the amount of stored body fat and the mobilization of fat is reflected in blood leptin concentrations, changes with regard to the concentration of this hormone in early lactation can be anticipated too [9,33]. Other hormones that tend to decrease during feed restriction and NEB are thyroid hormones [65] and insulin-like growth factors (IGF) [63]. These changes reflect the adaptational system of the cow which is activated in order to meet the demands for the increasing milk production and maintenance.…”
Section: Negative Energy Balance and Adaptation: Definition Quantifimentioning
confidence: 99%
“…Thyroid hormones are important physiological indices commonly used in studies concerning metabolic rate (Chen and Riley, 1981), animal thermogenesis (McGuire et al, 1991;Bird et al, 1998), central nervous system development and changes in cognitive function in animals and humans (Schantz and Widholm, 2001;Helmreich et al, 2006;Long and Voice, 2007). Their supplementation increases the metabolic rate and promotes significant weight loss with dietary restriction (Graves and Schott, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormones are important physiologic indices which are commonly used in metabolic rate and animal -E-mail: esterina.fazio@tin.it thermogenesis studies (McGuire et al, 1991;Bird et al, 1998) and their supplementation may increase metabolic rate and promote significant weight loss with dietary restriction. In addition, hormonally mediated events play an important role in central nervous system development and function, and a number of researchers have speculated that changes in cognitive function are also mediated by thyroid hormones in humans and animals (Schantz and Widholm, 2001;Helmreich et al, 2006).…”
Section: Introductionmentioning
confidence: 99%